Pengaruh Model Pembelajaran Koperatif Tipe Artikulasi terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Kelas V SDN Kota Bengkulu - Elin wahyulin; Resnani Resnani; Hasnawati Hasnawati (JURIDIKDAS, 2020)
This study aims to determine the application of the articulation type cooperative model to student learning outcomes in Thematic learning in class V SDN Bengkulu city. This research is a quantitative research.. The research method used is quasy experiment with the matching only pretest-posttest control group design research design. The population in this study were all Grade V Bengkulu City Vocational Schools that had used the 2013 curriculum and were accredited A. The sample in this study were VA grade students in 82 State Primary Schools in Bengkulu City and VC Grade Students in 61 Primary Schools in Bengkulu City with 64 students person. The sampling technique uses cluster random sampling, namely multistages cluster random sampling. The instrument used in the study was a test of learning outcomes in the form of multiple choice questions through pretest and posttest, the results of learning the attitude and skills aspects of the instrument used were observation sheets. To measure aspects of the knowledge of taking the test twice, namely before and after learning takes place in the experimental and control classes. Data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics. From the research results it is known that the results of the t-test for Indonesian subjects t-test was 4.27 and the Natural Science t-test was 3.60 with a t-table at a significant level of 5% of 1.67. The dimensions of t-count are greater than t-table. From these data it appears tahat there are differences in learning outcomes achieved by students in the experimental and control classes. Then there is the influence of articulation models on student learning outcomes in Thematic learning class V SDN Bengkulu City.